Human Herpesvirus‐6 Infectious Meningitis With Lymphadenitis in an Immunocompetent Adult - Yu Xie; Chenrui Zhang; Mingchi Ma; Ziqian Yin; Liqian Chen; Yimiao Yang; Shuang Wu; Yuanteng Fan; Yan Xu; Dan He (Brain and Behavior)
ABSTRACT Purpose Human Herpesvirus 6 (HHV‐6) infections are primarily observed in immunocompromised individuals, such as those with acquired immunodeficiency syndrome or organ transplant recipients. However, its role as a pathogen in immunocompetent adults remains debated. We aimed to explore the clinical significance of HHV‐6 in immunocompetent individuals by presenting a case of HHV‐6‐associated meningitis with concurrent lymphadenitis. Method We describe a case of an immunocompetent adult presenting with recurrent fever and headaches. Finding Diagnostic evaluations included next‐generation sequencing analysis identified HHV‐6 in both cerebrospinal fluid specimens and lymphoid tissue samples. The patient demonstrated complete clinical resolution following a 14‐day course of ganciclovir therapy. Conclusion This case underscores the need to consider HHV‐6 infection in immunocompetent adults presenting with meningitis of unknown etiology. Early detection and targeted antiviral therapy may lead to favorable clinical outcomes